Associations of dietary oxidative balance score with sarcopenia in adults: an NHANES-based cross-sectional study - Qiang Zhou; Shang Zhou; Zuo-xi Chen; Wu-jie Zhou; Jia Su; Yong Wang (Nutrition & Metabolism)
Abstract Background Sarcopenia, a prevalent muscle disorder in the older adults, is characterized by accelerated loss of muscle mass and function, contributing to increased risks of falls, functional decline, and mortality. The relationship between dietary oxidative balance score (DOBS) and sarcopenia, however, remains unclear. Methods We conducted a cross-sectional analysis of the National Health and Nutritional Examination Survey (NHANES) 2011–2018 cohort, which included 8,240 participants, aged 47.2 ± 17.6 years (48.6% male, 51.4% female). The participants were selected from geographic locations across all 50 states and the District of Columbia, using a stratified, multistage probability sampling design to collect health and nutritional data representative of the civilian, non-institutionalized U.S. population. We employed the generalized additive model to identify potential non-linear relationships and utilized the two-piecewise linear regression model to investigate the association between DOBS and sarcopenia in American adults. Results Participants were categorized into quartiles based on their DOBS, and sarcopenia was diagnosed in 702 individuals (8.5%). In the unadjusted model, DOBS exhibited a significant negative correlation with sarcopenia (β = 0.97, 95% Confidence Interval (CI): 0.96 to 0.99, P < 0.001). This association remained consistent in the model with minimal adjustment for age and gender (β = 0.97, 95% CI: 0.96 to 0.98, P < 0.001) and in the fully adjusted model including additional covariates (β = 0.97, 95% CI: 0.96 to 0.99, P < 0.001). After adjusting for potential confounders, we identified a non-linear association DOBS and sarcopenia, with an inflection point at 23. The effect sizes and CIs to the left and right of the inflection point were 1.62 (95% CI: 1.09 to 2.41, P = 0.016) and 0.97 (95% CI: 0.95 to 0.98, P < 0.001), respectively. Subgroup analyses confirmed the stability of this relationship across various demographic and health-related variables. Conclusions This research provides new insights into the association between diet quality, as assessed by DOBS, and sarcopenia, reinforcing the critical role of a balanced, antioxidant-rich diet in adult muscle.